Review of Legal Policy Concerning Payment of Book Royalties in Indonesia Based on Copyright Law - Dahris Siregar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to find out how the study of legal policy regarding payment of book royalties in Indonesia is based on the Copyright Act, the royalty payment system must of course be through an agreement between the two parties, namely between the publisher and the author of the manuscript. The agreement is made after the manuscript is received and deserves to be published by signing the SPPB (Book Publishing Agreement). The royalty amount for the purchase system is decided by mutual agreement between the publisher and the author. Publishers give royalties to authors in accordance with the general standard, which is 10%, it can be increased or less depending on how famous the author's denomination is and the superiority of the elbow grease produced. document as contained in clause 1 characteristic 1 of collection character 28 of 2014 in reference to document (UUHC) that "Copyright is the incompatible hold together of the originator that arises mechanically supported on declaratory customaries subsequently a elbow grease is accomplished in a touchable configuration without reduction the qualifications in conformation with with the refreshments of regulations and regulations". The refreshments in document be resonant the accomplishment and security of a elbow grease mechanically without continuance certified nailed down pronouncements and are extremely intimately related the continuance of the elbow grease and its originator if a elbow grease has been touchable and has incompatible rights which are dual-laned into economical Rights and conscientious Rights.